Debates in marketing orientation - Bozkurt, Bilgehan (Emerald Publishing Limited, 2019)
This book examines the fundamental problems and the alternative solutions of marketing orientation. Through a consideration of customer orientation and the marketing concept, Debates in Marketing Orientation considers the role of the individual in the marketing process.The debates reveal sources of managerial and cultural tension that can occur while trying to implement customer-oriented business processes at a marketing organization. How can academic and professional marketing perspectives be integrated? What are the main issues about understanding and analysing customer needs? What are the deepest roots of issues for organizations that aim to remain or become customer-oriented? Some of the interesting topics discussed are about academia and professional collaborations, demand management, stakeholder marketing, methodology development, marketing interfaces, new competition perspectives, managerial alternatives, mindsets, marketing skills, healthy organizations, marketing-driven operations, mixing branding constructs, integrative frameworks, human orientation, responsibility, ecosystems, organizational comfort zones, customer-driven organizational cultures, internationalization, and social impact. This book is a call towards a creative marketing concept as the core of post industry competition: where marketing is an alternative to management.
Keywords: Marketing.; Industrial organization.; Business & Economics -- Marketing -- General.; Sales & marketing.; elektronické knihy; electronic books